2013
DOI: 10.4028/www.scientific.net/amr.756-759.4604
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Model for the Batch Processing of Defective Products in Manufacturing and Remanufacturing

Abstract: This study focuses on simple stationary demand satisfied by the remanufacturing of products and the manufacture of new products. Further, we presented how to use batch processing to reduce defective products in the remanufacturing and the manufacturing inventory. In this paper, we obtain the economic order quantity of new products and the optimal inventory level of products that have been remanufactured as well as the appropriate return rate for the economic order quantity and the economic remanufacturing quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…With this in mind, we hope to use circular economy or recycling to reduce the consumption of the earth's resources. The past decade has seen a wide range of literature on reverse logistics (Chan, Yin, & Chan, 2010 [1]; Alamri, 2011 [2]; Mona 2011 [3]; Lin, C-C., 2013 [4]; Li, Y., & Chen, Z., 2015 [5]; Wakhid, A.J., Rahmad, S., Pringgo, W. L., 2018 [6]) and sustainable product design/manufacturing/operations (Yuan-Shyi, 2005 [7]; El Saadany & Jaber, 2010 [8], 2011 [9]; Gungor & Gupta, 1999 [10]; Jaber & El Saadany, 2009 [11], 2011 [12]; Hodgson & Warburton, 2009 [13]). Some recent reviews (Akcali & Cetinkaya, 2011 [14]; Lin, T-Y., 2013 [15]) have shown that inventory and production planning in a closed-loop supply chain are quantitative models.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we hope to use circular economy or recycling to reduce the consumption of the earth's resources. The past decade has seen a wide range of literature on reverse logistics (Chan, Yin, & Chan, 2010 [1]; Alamri, 2011 [2]; Mona 2011 [3]; Lin, C-C., 2013 [4]; Li, Y., & Chen, Z., 2015 [5]; Wakhid, A.J., Rahmad, S., Pringgo, W. L., 2018 [6]) and sustainable product design/manufacturing/operations (Yuan-Shyi, 2005 [7]; El Saadany & Jaber, 2010 [8], 2011 [9]; Gungor & Gupta, 1999 [10]; Jaber & El Saadany, 2009 [11], 2011 [12]; Hodgson & Warburton, 2009 [13]). Some recent reviews (Akcali & Cetinkaya, 2011 [14]; Lin, T-Y., 2013 [15]) have shown that inventory and production planning in a closed-loop supply chain are quantitative models.…”
Section: Introductionmentioning
confidence: 99%